Individual asymmetry profile and typological personality (The Journal of Psychology and Sociology, 2021)
This article examines the relationship between individual asymmetry and typological personality traits in adolescence, and also develops recommendations for improving the effectiveness of educational activities in adolescence. The study, which involved a total of 912 young people, was carried out in three stages. At the first stage of the study, 357 students of academic lyceums (74 girls and 283 boys) took part. The second stage of the study involved 244 students of vocational colleges (including 218 girls and 26 boys) and 80 conscripts. The third stage of the study involved 231 students (138 girls and 92 boys). The relationships identified between the individual profile of asymmetry and typological personality traits (cognitive style and style of activity, which are expressed in pragmatism, reflexivity, theoretical and practical style of thinking, in the features of verbal and non-verbal thinking, the leading signaling system, emotionality, figurative memory, volition, analytical abilities, self-regulation, etc.) made it possible to formulate scientifically grounded conclusions about the close relationship between the individual profile of asymmetry and typological personality traits. For example, if the functional test “Plexus of fingers” is mainly associated with such a personality trait as the ease of transition from thinking to practical action (pragmatism), then “Aiming” and “Applause” have a significant impact on the manifestation of the first and second signaling systems in personality. The functional test “Pose of Napoleon” serves as an impor- tant factor in the formation of the quality of extraversion-introversion of a person.Key words: individual profile of asymmetry, typological personality traits, adolescence, cognitive style, learning activity.